Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Akuntansi Mengikuti Pendidikan Profesi Akuntansi - Aurely, Sekar Hardya; Hendri, Nedi; Septiani, Ana (Expensive: Jurnal Akuntansi dan Keuangan, 2024)
This study aims to analyze Quality Motivation Career Motivation , Economic Motivation , Degree Motivation , USAP Motivation , Educational Cost Motivation , Educational Duration Motivation , Social Motivation , and Gender Motivation on Student Interest in PPA. The population in this study were 144 respondents. The sample in this study was obtained as many as 108 respondents. The data in this study used SPSS version 25 with multiple linear regression analysis testing. The results of this study indicate that quality motivation, career motivation, economic motivation, degree motivation, USAP motivation, tuition fee motivation, length of education motivation, social motivation, and gender motivation have a partial or simultaneous effect on student interest in participating in PPA on Undergraduate Accounting Study Program Students, Faculty of Economics and Business, Muhammadiyah Metro University.